HUBUNGAN KUALITAS TIDUR DENGAN LAMA HARI DIRAWAT PASIEN GASTRITIS DI RSU KEBUMEN - Safrudin ANS; Asrin -; Eti Purwatiningsih (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2009)
Sleep is a human basic need that is very influenced by factors such as physiology, psychology and life style. The people who are sick need to sleep and rest more than the others for their more easily recovery process. Gastritis is one of diseases that lessen the patient’s sleep quality. The patient will lose much energy that actually can be used for the recovery process and as the result, she/he becomes weak. The objective to prove the correlation between sleep quality with the treatment duration of gastritis patients in Kebumen General Hospital. The design used in the research was descriptive correlative design with cross sectional approach. The data were analyzed by using correlation Kendal Tau test to find out weather there was correlation between the variables. The sample were taken by using accidental sampling. The sample of the study were 20 respondents with inclusion and exclusion criteria. Research finding showed that the treatment duration at gastritis patient in the inside disease ward of Kebumen, the largest percentage of treatment duration at gastritis patient was shortly treatment that were 9 respondents (45%); description of sleeping quality at gastritis patient in the inside disease ward of Kebumen General Hospital with the largest percentage at adequate sleeping quality; there was significant correlation between sleep quality with the treatment duration of gastritis patients in Kebumen General Hospital with t-count 0.862 (p: 0.000). Conclusion: research finding showed there was significant correlation between sleep quality with the treatment duration of gastritis patients in Kebumen General Hospital. Keywords: sleep quality, the treatment duration, gastritis.